The Pre-Evaluation of Crosslinked Anion Exchange (CAX) Resin on Nitrates Removal - Aimi Asyiqin, Abu Kassim; Norhayati, Abdullah; Mohammad Zuhaili, Yahya (Universiti Malaysia Pahang, 2019)
This study is present the result of synthesizing crosslinked anion exchange (CAX) resin bearing quaternary ammonium functionalities. Crosslinked anion exchange of poly(HEMA-co-EGDMA-co-VBC) were synthesized via the modified suspension polymerization technique, then treated in hyper-crosslinking reaction to increase specific surface area (SSA) of CAX beads resin from ~5 to 124 m2/g and followed by amination treatment with N,N-dimethylbutylaminee (DMBA) to obtain CAX resin. After functionalized process, the amount of nitrogen content increased and intensity at 1265 cm-1 that assigned for chloromethyl group has decreased, showing that DMBA successfully being attached to the backbone. CAX resin was fully characterized by using Scanning Electron Microscopy (SEM), and Fourier Transform Infrared Spectroscopy (FT-IR) respectively. A pre-evaluation study was carried to investigate the performance of CAX beads resin to remove nitrate by using ion exchange method. Three parameters were used to study the sorption process; contact time, influent concentration and amount of resin used. For overall sorption, the sorption managed to obtain 88 % nitrate removal by using 0.5 g of CAX resin at 50 ppm influent concentration within 1-hour contact time and the highest adsorption of CAX achieved was 93 % removal of nitrate ions within 4-hours contact time.